Bolstering Confidence in Obesity Prevention and Treatment Counseling for Resident and Community Pediatricians - Perrin, Eliana M.; Jacobson Vann, Julie C.; Lazorick, Suzanne; Ammerman, Alice S.; Teplin, Sari; Wegner, Steven E.; Benjamin, John T. (East Carolina University, 2008)
Objective- To assess whether equipping resident pediatricians and community pediatricians with both training and practical tools improves their perceived confidence, ease, and frequency of obesity related counseling to patients. Methods- In 2005-2006, resident pediatricians (n = 49) and community pediatricians (n=18) received training regarding three evidence-based obesity prevention/treatment tools and responded to pre-and post-intervention questionnaires. We analyzed changes in reported mean confidence, ease, and frequency of dietary, physical activity, and weight status counseling. Results- Baseline scores of confidence, ease, and frequency of counseling were higher in community pediatricians than residents. Mean scores increased significantly in the combined group, among residents only, and trended towards improvement in the community pediatricians following the intervention. Means for "control" questions were unchanged. Conclusion- Training and tools for residents and community pediatricians improved their confidence, ease, and frequency of obesity-related counseling. Practice Implications- This study demonstrates that when feasible and appropriate tools and training were provided through a simple intervention, physicians gained confidence and ease and increased their counseling frequency. The results here suggest that widespread implementation of such educational interventions for community practitioners and practitioners in training could change the way physicians counsel patients to prevent the often frustrating problem of childhood obesity. Originally published Patient Education and Counseling, Vol. 73, No. 2, Nov 2008
Keywords: Childhood overweight; Counseling; Residency; Nutrition; Physical activity